Work Self-Efficacy and Engagement of Vocational Business Education Lecturers - Edokpolor, James; Otache, Innocent; Osifo, Kessington (Journal of Technical Education and Training, 2022)
While the job demands-resources theory proposed that work self-efficacy (a salient indicator of personal resources) plays a key role in predicting the work engagement of employees, empirical evidence supporting this assumption is limited, particularly in developing countries such as Nigeria. Against this background, the present study explores the interplay between work self-efficacy and work engagement of vocational business education (VBE) lecturers in public universities. The study adopted a quantitative approach and a survey research design. Data were collected from 139 lecturers in 12 public universities in Nigeria using a structured questionnaire. Pearson correlation coefficient and simple linear regression with a bootstrap bias-correction technique were used to analyse the data collected. The results show that work self-efficacy is positively and significantly correlated with the work engagement (cognitive, emotional, and physical) dimensions of VBE lecturers. Further analysis indicates that work self-efficacy is positively and significantly associated with the aggregate work engagement of VBE lecturers. The findings suggest that work self-efficacy helps foster a high cognitive, emotional, and physical engagement among VBE lecturers in public universities. The findings offer a major practical implication for lecturers and administrators, which suggests that VBE lecturers that are highly resourceful (i.e. self-efficacious) have the motivational potential to experience high engagement and, in turn, perform better on the job.